2018
DOI: 10.1155/2018/3502514
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molecular Mechanisms of Protein-Ligand Interactions by Molecular Docking and Molecular Dynamics Simulation: A Case of Oligopeptide Binding Protein

Abstract: Protein-ligand interactions are a necessary prerequisite for signal transduction, immunoreaction, and gene regulation. Protein-ligand interaction studies are important for understanding the mechanisms of biological regulation, and they provide a theoretical basis for the design and discovery of new drug targets. In this study, we analyzed the molecular interactions of protein-ligand which was docked by AutoDock 4.2 software. In AutoDock 4.2 software, we used a new search algorithm, hybrid algorithm of random d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(77 citation statements)
references
References 34 publications
(35 reference statements)
1
74
0
2
Order By: Relevance
“…The number of hydrogen bonds were calculated because this is another significant element influencing protein stabilization. The higher number of hydrogen bonds represents the higher stability of ligands with the proteins (Fu et al, 2018). In this study, the epitope YGIFAITAL showed maximum number of hydrogen bonds with both HLA proteins, which depicts the better binding ability of YGIFAITAL epitope.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The number of hydrogen bonds were calculated because this is another significant element influencing protein stabilization. The higher number of hydrogen bonds represents the higher stability of ligands with the proteins (Fu et al, 2018). In this study, the epitope YGIFAITAL showed maximum number of hydrogen bonds with both HLA proteins, which depicts the better binding ability of YGIFAITAL epitope.…”
Section: Discussionmentioning
confidence: 49%
“…We performed MD simulation calculation RMSD to observe the stability of the epitope-HLA complex. The higher RMSD value represents the higher flexibility of HLA-epitope binding (Dash et al, 2017;Fu, Zhao, & Chen, 2018). In case of bonding with HLA-C*03:03, YGIFAITAL was much more stable compared to KVLYGIFAI-HLA-C*03:03 throughout the simulations.…”
Section: Discussionmentioning
confidence: 97%
“…In immunoinformatics, one crucial use of molecular docking is the simulation of binding between T lymphocyte epitopes and their respective MHC molecules [197][198][199]. The binding affinity between a receptor and its ligand can be defined by the energy released during spontaneous bond formation between the two and the lower the energy, the more tightly bound the receptor is to its ligand [200,201]. Our selected 7 T lymphocyte epitopes had 32 corresponding MHC alleles ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking simulation is a study that conjures the orientation of ligand in the receptor (enzyme or protein) [18].…”
Section: Molecular Docking Simulations Of Ligandmentioning
confidence: 99%